Podophyllin 0.5% or 2.0% v podophyllotoxin 0.5% for the self treatment of penile warts: a double blind randomised study. Issue 3 (June 1997) - White, D J; Billingham, C; Chapman, S; Drake, S; Jayaweera, D; Jones, S; Opaneye, A; Temple, C
Abstract : OBJECTIVE: To compare the effectiveness and cost of self treatment of penile warts with a commercial preparation of podophyllotoxin 0.5% (PDX 0.5%) with podophyllin 0.5% and podophyllin 2.0% sourced from Podophyllum emodii. DESIGN: A prospective double blind randomised study. SUBJECTS: 315 patients with penile warts attending two departments of genitourinary medicine. MAIN OUTCOME MEASURES: Absence of warts, cessation of treatment due to severe side effects at 5 weeks. RESULTS: Of the 315 patients, 244 conformed to the protocol. Analysis was on an intention to treat basis. At 5 weeks no significant differences were found in the extent of healing of warts or in side effects for the three treatment groups. The costs of drug treatment (excluding staff time) are at least pounds 10.00 less for podophyllin than podophyllotoxin. A fourfold variation in the active constituents of the podophyllin preparations did not produce appreciably different clinical responses. In a subanalysis no evidence of deterioration in effectiveness of podophyllin over time was demonstrated. CONCLUSIONS: Penile warts in selected cases can be safely treated with 0.5-2.0% podophyllin self applied by the patient at a fraction of the cost of commercially available podophyllotoxin. The shelf life of the podophyllin extracts is at least 3 months. These findings may be especially relevant in countries where resources for health care are limited.